If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3X + -4(-6X + 7W) + 4 = 0 Reorder the terms: -3X + -4(7W + -6X) + 4 = 0 -3X + (7W * -4 + -6X * -4) + 4 = 0 -3X + (-28W + 24X) + 4 = 0 Reorder the terms: 4 + -28W + -3X + 24X = 0 Combine like terms: -3X + 24X = 21X 4 + -28W + 21X = 0 Solving 4 + -28W + 21X = 0 Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -28W + -4 + 21X = 0 + -4 Reorder the terms: 4 + -4 + -28W + 21X = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -28W + 21X = 0 + -4 -28W + 21X = 0 + -4 Combine like terms: 0 + -4 = -4 -28W + 21X = -4 Add '-21X' to each side of the equation. -28W + 21X + -21X = -4 + -21X Combine like terms: 21X + -21X = 0 -28W + 0 = -4 + -21X -28W = -4 + -21X Divide each side by '-28'. W = 0.1428571429 + 0.75X Simplifying W = 0.1428571429 + 0.75X
| X-2/3=5-3/2x-2/3 | | 4x+10=10x+3 | | 47-12x+38=x+59 | | M+n+2=m+2+n | | y^2+x^2=2rx | | 2y+16=38 | | 7.5x-4=-28+1.5x | | (9x+4)(9x+4)=32 | | 4m-3=3+m | | =(2x+3y)(3x-y)(-4x+y) | | (2x+3y)(3x-y)(-4x+y)= | | 0.3(2x-1)-2.3=0.04(x+4) | | 48+7*x=10x-4 | | 12=4(w-13)-8 | | gal=20 | | .1(x)+.07(170000-x)=1475 | | -5+16x+5x*x=10x+15 | | gal=20l | | x*0.6=x-50 | | 2(v+5)-10=10 | | 4x+8-x-3=23 | | 3(k+4)-9=9 | | x-(x/0.6)=50/0.6 | | 2(2x-4)=6(x-2) | | 40+7*x=10x-4 | | 2(2x-4)=6(x-4) | | 1=j-6/2 | | 2(w-7)-2=2 | | g-10/-3=0 | | 20r+5s-7r+9s= | | 54p=27 | | 56=8(x) |